A STUDY OF METAPHORIC MEANINGS OF WORDS DENOTING WEATHER IN ENGLISH AND VIETNAMESE - Ph.D LÊ TẤN THI (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims to investigate the metaphoric meanings of words denoting weather in English and Vietnamese. It also finds out and explains the similarities and differences between the two languages so as to have a new look at the diversity in the meanings of words denoting weather in both languages.